Spiritual Migration and Social Response: The Khuruj fï Sabïlillah Program of Tablighi Jamaat Movement in Palopo City - Marzuki, Asgar; Usman, Syahruddin; Kasim, Amrah; Kamaluddin, Munawir Kamaluddin (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to describe the community response and implementation of the Khuruj fï Sabïlillah program using the Tarbiyah Iṣlähiyah method as an effort to improve the community by the Jama'ah Tabligh in Palopo City. The type of research used is qualitative descriptive analysis with a phenomenological approach. Data collection was conducted using in-depth interviews, participant observation, and documentation studies. The collected data were analyzed using an interactive analysis model with three forms of activities: data condensation, data display, testing the validity of data, data triangulation, then drawing research conclusions as the final process to answer questions from the research. The results of the study show the response of the Palopo community to the khuruj fī sabīlillāh program is generally positive as an expression of religious life, supported by the charismatic ulama known as the “Lima Serangkai” and reinforced through synergy with traditional leaders, government authorities, and established Islamic organizations, while any opposition identified is individual in nature and does not reflect collective public attitudes. The implementation of the program largely depends on the capacity of the murabbi as the main field executor, making the selection of individuals with strong religious competence, emotional stability, and experience in mentoring new participants crucial; although the program has reached all segments of society, its sustainability and fidelity to core values require consistent follow-up, continuous supervision, and objective evaluation down to the lowest mahallah level. This study highlights the importance of cultural context and leadership in the success of the khuruj fī sabīlillāh program in Palopo. Theoretically, it demonstrates the strength of community-based movements with murabbi as key spiritual leaders, while practically it calls for adaptive tarbiyah iṣlāḥiyah to develop the program as a model for empowering religious practice.